Acid Whey from Industrial Greek Strained Yoghurt: Effect of the Kind of Milk and the Way of Straining on Its Composition and Processing by Nanofiltration - Marianna Karela; Lambros Sakkas; Evangelia Zoidou; Golfo Moatsou; Konstantina Milosi; Ekaterini Moschopoulou (Dairy)
The acid whey derived during the production of Greek yoghurt, i.e., yoghurt acid whey (YAW), is considered as environmental pollutant due to its low pH and high lactose content. YAW may be obtained by centrifugation or ultrafiltration or filtration through cloth bags (traditional method) of the initial yoghurt, methods that could affect its composition. In the last years, efforts have been made to improve its composition using membrane technology. In the present work, the composition of 35 different YAW samples from Greek Yoghurt dairies was studied. The YAW samples were grouped according to the way of production and the kind of milk in the case of the traditional method. The results showed that both the kind of milk and the way of yoghurt staining affected its composition. Ovine YAW derived from traditional straining was richer in lactic acid and calcium than bovine YAW. Moreover, the composition of bovine YAW varied among the different ways of straining, and this affected its behaviour during membrane processing. Nanofiltration of three representative bovine YAW samples and one ovine YAW sample at their natural pH, i.e., pH 4.5, and at 25 °C removed the lactic acid at a range from 40 to 55%, and the monovalent cations > 60% and retained lactose and galactose at percentages > 95% and 80% respectively.